Embodied risk for families with Li-Fraumeni syndrome: Like electricity through my body. (May 2022) - Werner-Lin, Allison; Forbes Shepherd, Rowan; Young, Jennifer L.; Wilsnack, Catherine; Merrill, Shana L.; Greene, Mark H.; Khincha, Payal P.
Abstract: Introduction: Experiences of illness change the physical body and embodiments, or the ways in which the world and the self are known through the body. When illness is anticipated, such as with inherited cancer predisposition syndromes, risk becomes embodied and shared in family groups. Embodied risk is experienced whether or not symptoms have manifested. To examine how individuals and families with genetic risk experience the world and understand their disease through their bodies, we employ Li-Fraumeni syndrome (LFS) as an exemplar. LFS is a rare, genetic, cancer predisposition syndrome with nearly 100% lifetime cancer risk starting from birth, limited opportunities for prevention, rigorous screening protocols, and early mortality. Methods: Forty-five families, including 117 individuals aged 13–81 years, enrolled in the National Cancer Insitute's LFS study (NCT01443468) completed 66 open-ended interviews regarding LFS experiences. An interdisciplinary team used modified grounded theory to explore physical aspects of living with LFS in psychosocial contexts. Findings: The physicality of living with LFS included constant monitoring of LFS bodies across the family to identify physical change that might indicate carcinogenesis. Cancer screening, risk reduction, and treatment acted as dually protective and invasive, and as an unavoidable features of LFS. Connections between family members with similar embodiments normalized aesthetic changes and supported coping with visible markers of difference. In some circumstances, participants objectified the body to preserve the self and important relationships. In others, intense pain or loss created thresholds beyond which the self could no longer be separated from the body to support coping. Discussion: This paper focuses on Li-Fraumeni syndrome, a familial condition with a well-established genetic identity in which the body-self is experienced in relation to important others, to medical imaging, and to historical experiences with cancer. We expand on theories of embodied risk and inter-embodiment to describe experiences across disease trajectories, with attention to division and union between body, self, and other. Highlights: Embodiments of genetic risk are formed in social, medical, and historical contexts. Embodiments of cancer risk are shared in families with heritable genetic mutations. Cancer risk management may be protective, yet also invasive and unavoidable. Inter-embodiments normalize treatment-based aesthetic and functional change. Division and union between body, self, and other may facilitate coping with risk.